The Influence of Service Quality and Customer Relationship Marketing on Tourist Loyalty with Trust as a Mediating Variable at Sana Vie Villa Seminyak - Rusmiati, Ni Nyoman; Nugraha, Surya; Budiasa, I Ketut (Akademi Komunitas MAPINDO, 2024)
Sana Vie Villa Seminyak is a hotel industry that can contribute to the economy of the community in theSeminyak Traditional Village and its surroundings. The sustainability of Sana Vie Villa Seminyak cannot beseparated from the role of consumers or tourists who stay there, because consumers or tourists are the reasonwhy Sana Vie Villa Seminyak can continue to exist today. This research aims to determine the influence ofservice quality and customer relationship marketing on tourist loyalty with trust as a mediating variable. Thisresearch was conducted at Sana Vie Villa Seminyak. Samples were determined using the Slovin formula with asample size of 100 samples. Data collection in this research used questionnaires with the data analysistechnique SEM-PLS. The results of this research show that e-service quality has a positive effect on touristloyalty. Customer relationship marketing has a positive and significant effect on tourist loyalty. Trust has apositive and significant effect on tourist loyalty. service quality has a positive and significant effect on trust.Customer relationship marketing has a positive and significant effect on trust. Trust is able to mediate theinfluence of service quality on tourist loyalty. Trust is able to mediate the influence of customer relationshipmarketing on tourist loyalty.Keywords: Service Quality, Customer Relationship Marketing, Tourist Loyalty, Trust